If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + p + 14 + p * 3 + -32 = 612 Reorder the terms for easier multiplication: p + p + 14 + 3p + -32 = 612 Reorder the terms: 14 + -32 + p + p + 3p = 612 Combine like terms: 14 + -32 = -18 -18 + p + p + 3p = 612 Combine like terms: p + p = 2p -18 + 2p + 3p = 612 Combine like terms: 2p + 3p = 5p -18 + 5p = 612 Solving -18 + 5p = 612 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 5p = 612 + 18 Combine like terms: -18 + 18 = 0 0 + 5p = 612 + 18 5p = 612 + 18 Combine like terms: 612 + 18 = 630 5p = 630 Divide each side by '5'. p = 126 Simplifying p = 126
| 15x*6=71+10x | | 30x^2+11x-19=0 | | x^2+y^2-6x+8y+16=0 | | 4(2w-5)=3w+10 | | 5(3x+4)=5*3x | | i=ec | | 1/3(m+2)=1 | | 5(3x+4)=3x(4+6) | | (3xy+3y^4)dx+(2x^2+5xy^3)dy=0 | | 5(2x+3)=6(3x+2) | | 2x^3-3x+1=0 | | x^3-60x^2-162=0 | | 16t^2-17t+4=8 | | b+hy=l | | 3(2*1)=4x+3+2x | | 16T^2-17T+12=0 | | -19-h-h=-13 | | .6+b=-2.5 | | 1.3*3+6=2x-3-9 | | 4(5-x)=3x-2 | | 0.6(0.1x+0.9)= | | -x^2+x+8=0 | | x+2x+19+x=143 | | -x+7=-3x | | 7/5+b=17/5 | | 5x-2=8x | | 4(x-4)-2(x-3)+3x= | | 3=11n | | .8x-(.7x+.36)=7.1 | | 15-13(x-2)=2x+1 | | 1=6p-2 | | 20=e-8-5-12 |